2022
DOI: 10.3390/brainsci12121600
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Carotid Atherosclerosis Progression: Evidence from an Ultrasonography Laboratory

Abstract: Background and purpose: The purpose of this study was to investigate the role of risk factors in predicting the variation in carotid atherosclerosis at ultrasonographic follow-up and, therefore, its role in the progression of large-vessel disease. Methods: This retrospective population study included all the outpatients that underwent at least two carotid ultrasonographies at our laboratory from 2001 to 2017. Demographic data, vascular risk factors, and the results at follow-up were analysed to determine if co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Early identification of high-risk features through Neurosonology expedites intervention in strokes of various etiologies ( 5 ). Furthermore, Neurolosonolgy follow-up enhances the precision of therapeutic strategies, adding predictive information ( 6 ).…”
mentioning
confidence: 99%
“…Early identification of high-risk features through Neurosonology expedites intervention in strokes of various etiologies ( 5 ). Furthermore, Neurolosonolgy follow-up enhances the precision of therapeutic strategies, adding predictive information ( 6 ).…”
mentioning
confidence: 99%
“…Kadir et al 9 reported that NAFLD can be used as an independent risk factor for predicting subclinical atherosclerosis, which is closely related to cardiovascular events, and carotid plaque is a strong predictor of cardiovascular events 10 . Carotid ultrasound follow-up plays an important role in the monitoring and management of adverse cardiovascular events and can be used to noninvasively monitor the presence of subclinical atherosclerosis 11 . Studies have shown that FP is independently correlated with carotid intima-media thickness (CIMT) 12 .…”
mentioning
confidence: 99%